2012
DOI: 10.3382/ps.2011-01980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 types of broths and 3 selective agars for the detection of Campylobacter species in whole-chicken carcass-rinse samples

Abstract: In this study, we compared the effectiveness of 2 types of Bolton broths and 3 selective media for isolating Campylobacter spp. from naturally contaminated whole-chicken carcass-rinse samples. One hundred chickens were rinsed with buffered peptone water, and the rinses were added to 2× Bolton broth (with or without blood supplementation). The samples were incubated and then streaked onto Preston agar, modified cefoperazone charcoal deoxycholate agar (mCCDA), and Campy-Cefex agar, which was followed by incubati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…from poultry meat . This could be supported by the results obtained by Chon et al, (2012) who found that the number of agar plates that showed positive results for Campylobacters was significantly higher with the use of PA than with the use of modified Charcoal Cefoperazone Deoxycholate agar (mCCDA)and Campy-Cefex agar (CCA) when compare the performance of the three selective media used for detecting Campylobacters in carcass-rinse samples in Korea , and attributed to that mCCDA and CCA contain only one antibiotic, cefoperazone while PA contains four selective antibiotic agents . Furthermore, fewer PA plates showed contamination than the other media plates, indicating the superior selectivity of PA .…”
Section: Isolation and Identification Of C Jejuni Isolates Isolatesupporting
confidence: 82%
See 1 more Smart Citation
“…from poultry meat . This could be supported by the results obtained by Chon et al, (2012) who found that the number of agar plates that showed positive results for Campylobacters was significantly higher with the use of PA than with the use of modified Charcoal Cefoperazone Deoxycholate agar (mCCDA)and Campy-Cefex agar (CCA) when compare the performance of the three selective media used for detecting Campylobacters in carcass-rinse samples in Korea , and attributed to that mCCDA and CCA contain only one antibiotic, cefoperazone while PA contains four selective antibiotic agents . Furthermore, fewer PA plates showed contamination than the other media plates, indicating the superior selectivity of PA .…”
Section: Isolation and Identification Of C Jejuni Isolates Isolatesupporting
confidence: 82%
“…The corner was aseptically cut ,then 25 ml of the carcass rinse was placed by a disposable syringe in a sterile bottle containing 100 ml of Preston broth and pre-enriched for 4 hours at 37°C in an anaerobe jarunder microaerophilic condition , then enriched at 42°C for 24 hours. Lids on the bottles were loosened to allow rapid equilibration of their contents with the gas jar atmosphere (Chon et al ., 2012). After enrichment, one loopful of the medium was streaked onto Preston selective agar [ Campy agar base(Oxoid,CM 0689B) supplemented with antibiotics (Oxoid, SR 0204E) and Campylobacter growth supplement (Oxoid, SR 0232E) ] ; and onto Blood agar and parallel streaks were made using sterile loops to obtain discrete colonies .…”
Section: B Collection and Processing Of Broiler Chicken Carcasses (Bmentioning
confidence: 99%
“…Our results are consistent with the outcome of other studies. In our previous studies, we biochemically confirmed contaminants that appeared on cefoperazone‐based selective agars such as Campy‐Cefex agar and mCCDA, and most of the contaminants were identified as E. coli (Chon and others , b). Jasson and others () found that ESBL‐producing E. coli may profusely grow on cefoperazone‐based Campylobacter selective agars reducing recoveries of Campylobacter , because the ESBL enzyme blocks the antibiotic effect of cephalosporins.…”
Section: Resultssupporting
confidence: 61%
“…ESBL‐producing E. coli in selective agars is one of the most common factors that interfere with Campylobacter isolation from poultry meat, because dense ESBL‐producing E. coli on plates may mask Campylobacter colonies leading to false negative results (Jasson and others ; Moran and others ; Chon and others , b). However, a high concentration of polymyxin B, which is effective for Gram‐negative bacteria, may eliminate ESBL‐producing E. coli in the chicken carcass rinse.…”
Section: Resultsmentioning
confidence: 99%
“…The incorporation of either of these compounds appears to be a matter of cost. The use of filters also improves the performance of blood media, such as Campy-Cefex, which appears to have low selectivity and isolation rate because of the growth of competing microorganisms (Chon et al, 2012).…”
Section: Campylobacter Plating Mediamentioning
confidence: 99%